Factors Related to Nurse Compliance in The Implementation of Universal Precaution in The Inpatient Room One of Private Hospital in Yogyakarta - Siti Kurnia Widi Hastuti; Annisa Intan Fadilla; Selly Apriansyah (Universitas Muhammadiyah Yogyakarta, 2021)
Transmission of nosocomial infections from person to person must be prevented by always maintaining hand hygiene after carrying out inspection activities and interaction activities in hospitals, one of them by doing hand hygiene. Awareness of the importance of hand hygiene in health workers is needed in efforts to prevent nosocomial infections. The hand hygiene compliance rate obtained at One of Private Hospital in Yogyakarta is 80%. Awareness of the importance of the implementation of hand hygiene does not yet exist or has not emerged in the nurse itself, while it is very important in addition to protecting himself from the transmission of infection and can reduce the risk and spread of nosocomial infections in the hospital. This study uses an observational analytic method with a cross-sectional design. The sampling technique uses proportional random sampling, with the number of samples studied as many as 89 people. The research data were analyzed using the chi-square test. The p-value of 0.040 (p <0.05) indicates that there is a relationship between knowledge and nurse compliance in the implementation of hand hygiene. A p-value of 1.00 (p> 0.05) indicates that there is no relationship between attitude and nurse compliance in the implementation of hand hygiene. P-value of 0.425 (p> 0.05) indicates that there is no relationship between motivation and nurse compliance in the implementation of hand hygiene